In Vitro Digestibility Value of MA-11 Fermented Organic Materials of Organic Cassava Peel as Animal - Nastava, Devy Marselina; Sukaryani, Sri; Purwati, Catur Suci (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
By identifying and resolving these problems, research can make a greater contribution to the use of cassava peel as quality and safe animal feed, and can provide clearer guidance for livestock practitioners. This research aims to determine whether the use of MA-11 can affect the digestibility of dry matter and organic matter in cassava skin, so that it can provide additional information regarding the quality of fermented and unfermented cassava skin. This research was designed using a Randomized Random Design (RAL), which consisted of 3 treatments and 4 replications. The treatment given to cassava skin was P0: Cassava skin fermented with MA-11 0 ml, P1: Cassava skin fermented with MA-11 as much as 1 ml, P2: Cassava skin fermented with MA-11 as much as 2 ml. The research results showed that the average KcBK value was P0: 60.57%, P1: 65.08%, P2: 66.98%. The mean KcBO value obtained was P0: 67.20%, P1: 69.47%, P2: 71.22%. The conclusion obtained in this research is that the cassava peel fermentation process using probiotic MA-11 for 14 days with different levels has a very significant effect on the digestibility of dry ingredients and has a significant effect on the digestibility of organic ingredients that have been carried out.